2020
DOI: 10.1055/a-1152-5028
|View full text |Cite
|
Sign up to set email alerts
|

Squat Muscle Activation Patterns with Hip Rotations in Subjects with Genu Varum Deformity

Abstract: The purpose of this study was to compare muscle activation during the squat with different hip rotations (neutral, 15, 30, and 45° of internal and external hip rotation) in subjects with and without Genu Varum deformity deformity. Surface electromyography were recorded from 32 men with (n=16) and without (n=16) Genu Varum deformity. In the Genu Varum deformity group, the squats with 30, 45 and 15° of internal rotations of the hip showed significantly greater gluteus medius activation as compared to other posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…On the other hand, the synergist muscles work together and affect each other [13][14][15][16] , therefore it is important to examine them together in electromyography studies. Because it is shown that muscle imbalance or changes in muscle activity patterns between them are associated with non-contact injuries such as PFPS and ITBS 7 .…”
Section: Gvdmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the synergist muscles work together and affect each other [13][14][15][16] , therefore it is important to examine them together in electromyography studies. Because it is shown that muscle imbalance or changes in muscle activity patterns between them are associated with non-contact injuries such as PFPS and ITBS 7 .…”
Section: Gvdmentioning
confidence: 99%
“…In a similar study of isometric hip external rotation during single-leg stance, Schmitz et al 20 detected an increase in Gmed activity in response to isometric hip external rotation force. On the other hand, changes in the positions of hip rotations have been shown to be associated with changes in Gmed activity and can cause altered lower extremity alignment or be itself affected by postural malalignment 13 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that biomechanical deficiencies including excessive adduction and internal rotation of the hip and tibiofemoral external rotation and, subsequently altered muscle activity patterns during functional activities can be associated with overuse injuries [3][4][5][6][7]. Thus, it is important to assess and correct the movement defects, otherwise, over time this can cause more malalignment, exacerbating the symptoms of osteoarthritis, increasing the risk of overuse injuries such as iliotibial band and patellofemoral pain syndromes, and leading to other problems [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the synergist muscles work together and affect each other [11][12][13][14], therefore it is important to examine them together in electromyography studies. Because it is shown that muscle imbalance or changes in muscle activity patterns between them are associated with non-contact injuries such as PFPS and ITBS [5].…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study of isometric hip external rotation during single-leg stance, Schmitz et al [18] detected an increase in Gmed activity in response to isometric hip external rotation force. On the other hand, changes in the positions of hip rotations have been shown to be associated with changes in Gmed activity and can cause altered lower extremity alignment or be itself affected by postural malalignment [11,19].…”
Section: Introductionmentioning
confidence: 99%